THE ORIGIN AND EARLY DIVERGENCE OF THERAPSIDS - Ivakhnenko M.F. (My University, 2002)
The study of the temporal area of skulls in various theromorph groups demonstrated that the Ophiacodontia retain a primitive epipteric cavity between the braincase wall and the adductor fossa, which is limited laterally by the palatoquadrate structures (epipterygoid and quadrate); in the Sphenacodontia, the lateral wall of the cavity is reduced and the adductor musculature approaches the lateral surface of the braincase. This process progressed in primitive therapsids (Eotheriodontia: Gorgonopia, Dinocephalia, and Anomodontia). In higher therapsids (Eutheriodontia: Scaloposauria, Therocephalia, and Cynodontia), the epipteric cavity is retained but its lateral wall in the periotic region is formed by the squamosal. As a result, the Sphenacodontia and Eotheriodontia form a morphologically uniform group that should be opposed to the Eutheriodontia.